OP0028 Independent and Interactive Effects of Interferon (IFN)-Alpha and the Lupus Risk Haplotype HLA-DRB1*03:01 on Gene Expression in Ex Vivo B Cells. (9th June 2015) - Duarte, C.; Vyse, T.; Boteva, L.; Fernando, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex genetic autoimmune disease characterised by B cell hyperactivity and up-regulation of type I IFN. The DRB1*03:01 extended haplotype confers the greatest genetic risk for SLE in Europeans, but the molecular mechanisms underlying this association are unclear. Both coding and non-coding genetic variants arising from this haplotype may contribute to disease risk, implicating a role for gene regulation. Genetic effects on gene expression are context-specific, depending on factors such as cell type and cell state. Objectives: To investigate the effect of (i) IFN-α stimulation, (ii) DRB1*03:01 haplotypes and (iii) the haplotype-environment interaction between DRB1*03:01 and IFN-α on differential gene expression in ex vivo B cells. Methods: RNA was extracted from ex vivo CD19+ B cells from 50 healthy European women harbouring DRB1*03:01 homozygous (n=17), heterozygous (n=3) and non- DRB1*03:01 (n=30) haplotypes. Gene expression from cells at rest (n=49) and after stimulation with IFN-α for 6 hours (n=33) was quantified using the Affymetrix Human Exon 1.0 ST array. The individual and interactive effects of IFN-α stimulation and the DRB1*03:01 haplotype on gene expression were analysed using a two-way ANOVA (FDR 5%) using Partek Genomics Suite. Pathway and disease enrichment were analysed using Ingenuity Pathway Analysis. Results: 6, 906 out of 15, 468 genes are significantly differentially expressed in IFN-α-treated compared to resting cells, of which 1, 263 have fold changes >2. As expected, the data is enriched for the IFN-α pathway (P=3.4x10 -2 ) and B cell receptor signalling genes (P=2.1x10 -12 ). Approximately 60% of SLE- and rheumatoid arthritis-associated genes from GWAS are significantly enriched in this dataset (PSLE =4.4x10 -2, PRA =6.1x10 -6 ), in comparison to the non-autoimmune disease osteoarthritis (20%; POA =0.6). Interestingly, IFN-α affects SLE-associated genes outside canonical type I IFN and B cell signalling pathways, such as ITGAM (P=1.9x10 -10, ↓) and PTPN22 (P=4.5x10 -10, ↓). Genes implicated in monogenic SLE such as TREX1 and DNASE1L (DNA repair) and C1R (complement pathway) are also differentially expressed on IFN-α stimulation. The only gene significantly differentially expressed between DRB1*03:01 and non- DRB1*03:01 samples is BTN3A2, which is downregulated in DRB1*03:01 haplotypes in both resting (P=2.3x10 -2 ) and IFN-α-treated cells (P=1.2x10 -2 ). Furthermore, BTN3A2 levels differ between DRB1*03:01 and non- DRB1*03:01 individuals in response to IFN-α stimulation, implicating haplotype-environment interactions (Pint =1.4x10 -7 ). Conclusions: Stimulation of B cells with IFN-α influences the expression of genes associated with complex and monogenic forms of SLE not known to be involved in type I IFN or B cell signalling pathways. Individuals harbouring DRB1*03:01 haplotypes demonstrate downregulation of BTN3A2, implicating effects independent of HLA alleles for this risk haplotype. Additionally, we show that IFN-α and DRB1*03:01 interactively downregulate BTN3A2, shedding some light into the mechanism behind the known association of IFN-α exposure with SLE risk. Investigating the effects of disease-associated haplotypes on gene expression in relevant contexts such as IFN-α stimulation may help in resolving genetic associations and identifying candidate genes underlying susceptibility to complex diseases. Disclosure of Interest: None declared